Prediction and analysis of combustion products in a spark ignition engine through Mathematical Modeling - Lira Cacho, Guillermo (2001)
The theoretical foundations of a zero dimensional numerical simulation mathematical model for the prediction and analysis of the main emissions of combustion products in a spark ignition internal combustion engine (E.CH.) are presented. The model is based on the numerical solution of the energy conservation, continuity and ideal gas equations of state. In the combustion phase, it is considered that this takes place in two zones. During the combustion and expansion phases, chemical equilibrium equations are used for the gas zone, products of combustion. Furthermore, in the determination of nitrogen monoxides (NO) and carbon monoxides (CO), chemical kinetic equations are used to contemplate the "freezing" effect. Finally, the analysis of the results obtained from the developed program.